A Quantitative Relationship Analysis of Industry Shifts and Trade Restructuring in ASEAN Based on Multiregional Computable General Equilibrium Models. (5th February 2021) - Xu, Luyuan
Abstract : This paper provides an in-depth study and analysis of the quantitative relationship between ASEAN industry transfer and nuclear trade restructuring through the multiregional computable general equilibrium (CGE) model and categorizes the ten major projects and 57 subprojects covered by the ASEAN Information Port project investment into construction, information technology, and telecommunications, according to the key directions of investment. We design and simulate the changes in production activities, trade activities, and the balance of payments behaviour of the national economy affected by the project's investment under 10 types of investment amount scenarios and prepare the corresponding social accounting matrix (SAM). Increased trade openness increases external risks and instability of the economy and fiscal revenues. At the same time, it creates other potential problems for the country such as environmental pollution and leading to unfair competition. Under free trade conditions, some manufacturers may choose to produce inputs that are not environmentally friendly to reduce costs, thereby harming the environment. For infant industries, if the government does not provide them with short-term protection or supportive policies, these new or developing infant industries may not have strong international competitiveness and may be vulnerable to the attacks of mature industries in the world. Therefore, based on the study of the influence of tax policy on trade openness, this paper examines the impact of changes in trade openness on a country's economic environment and takes tax revenue as an example to conduct an empirical analysis and improve the factors that need to be considered when adjusting tax policy.